Evaluation of Oncological Safety of Fat Grafting After Breast-Conserving Therapy: A Prospective Study - Mestak, Ondrej; Hromadkova, Veronika; Fajfrova, Monika; Molitor, Martin; Mestak, Jan (Annals of surgical oncology, 2016)
Introduction Breast-conserving treatment (BCT) consisting of a lumpectomy followed by radiation is considered the standard of care in early-stage breast cancer, and breast reconstruction using fat transfer has become the standard of care in these patients. Immediately following BCT, patients are theoretically the most prone for cancer recurrence caused by the remaining mass of glandular tissue. Therefore, we conducted a prospective study to evaluate the oncological safety of fat grafting in patients after BCT. Methods We analyzed patients who underwent breast reconstruction after BCT between April 2011 and February 2014. The control subjects were matched from a prospective database of women treated for breast cancer who did not undergo fat grafting, and each control was matched for the following variables: date of primary cancer surgery, date of fat grafting, histology, estrogen and progesterone receptors (ER+PR), adjuvant hormone therapy, disease-free interval from primary operation (BCT), and disease-free interval from breast reconstruction involving fat grafting. The primary endpoint of this study was tumor recurrence. Results The study group consisted of 32 patients, while the control group consisted of 45 patients. Breast tumor recurrence was observed in 2 of 32 cases (6.25 %) in the reconstruction group, and distant metastases were detected in both cases. In the control group without reconstruction, we found cancer recurrence in 2 of 41 cases (4.88 %), and locoregional recurrence was observed in both cases. The difference in cancer recurrence after BCT was insignificant between groups ( p = 0.593). Conclusion The recurrence rate in patients reconstructed with fat grafts after BCT was not significantly different from the recurrence rate of control BCT patients.